FACTORS AFFECTING BEHAVIORAL INTENTION IN USING GO-PAY WITH THE MODIFIED UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 2 MODEL (UTAUT2) - Alfia Nuriska; Salamatun Asakdiyah; Rai Raka Setyawan (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2018)
The development of payment systems in Indonesia is in line with the global technological advancements and followed by new innovations, including the presence of e-money.As a subsidiary of PT Aplikasi Karya Anak Bangsa (Go-Jek), PT Dompet Anak Bangsa is the holder of the Go- Pay e-money license and included as one of 32 companies that have obtained license as e-money operators from Bank Indonesia. Despite the current high transaction growth of Go-Pay, it may not survive without any efforts to improve its service quality and expand the consumer preferences in using Go-Pay. Therefore, it is necessary to identify the factors that influence behavioral intention in using Go-Pay. This study aims to examine and determine the factors that influence behavioral intention in using Go-Pay with the modified Unified Theory of Acceptance and Use of Technology2 Model (UTAUT 2). This study uses a quantitative method with a questionnaire as the research instrument. The population of this study is Go-Pay users in the Special Region of Yogyakarta. The method of data analysis is SEM-PLS. The results showed that there were three factors that were significant in influencing people’s interest in using Go-Pay, namely: Habit, Facilitating Condition, and Price Value.